TANTANGAN DAN TRANSFORMASI: SELF-CONTROL BAGI PRISMA (PEREMPUAN SINGLE MALAYSIA) DENGAN DOUBLE BURDEN - Gunarti, Tri Tami (MIYAH : Jurnal Studi Islam, 2024)
Abstract: The aims to delve into the enhancement of self-control levels among Prisma (single Malaysian women) facing double burdens in the Solokuro District. Involving an analysis of internal and external factors, this study identifies elements such as age, parental roles, response to failure, communication style, and participation in religious social activities as significant contributors to the development of self-control in Prisma women. External factors like the environment and family roles, including a positive disciplinary approach, were also found to play crucial roles in shaping individuals' ability to exercise self-control. Confronting the challenges of dual responsibilities in domestic tasks and productive work, Prisma women in the Solokuro District demonstrated adaptive and resilient self-control strategies, enabling them to remain productive and harmonious. The village government plays a role in empowerment efforts through Women's Association activities and parenting programs, focusing on economic independence through skill training and support in managing caregiving tasks. The findings contribute to understanding the dynamics of Prisma women experiencing a double burden, laying the groundwork for more effective empowerment policies and programs. In conclusion, strengthening the self-control of Prisma women is a key aspect in navigating the complexity of double burdens, and collaborative efforts among individuals, communities, and the government can positively impact their well-being and contributions to society. Keywords: Self-Control; Prisma; Double Burden; Solokuro